Development of an accelerated artificial ageing method for the characterization of degradation products of antioxidants in lubricants by mass spectrometry. Issue 3 (June 2019) - Kassler, Alexander; Pittenauer, Ernst; Doerr, Nicole; Allmaier, Guenter
The understanding of ageing mechanisms of antioxidants in base oils is indispensable for the development of improved lubricants. In this study, a novel artificial ageing method based on the application of peroxide as oxidant is presented for improved monitoring of thermo-oxidative degradation processes in combination with mass spectrometry. Model oils containing aminic and phenolic antioxidants were aged and chemical structures of their oxidation products were elucidated by ultrahigh performance liquid chromatography and electrospray ionization high resolution (Orbitrap) mass spectrometry. Additionally, synergistic mixtures of four antioxidants were investigated, because the formation of condensed molecules from amines and phenols would have a major influence on the antioxidant potential but could not be detected in the bulk lubricant.